2019
DOI: 10.21608/evmspj.2019.145815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Poly lactide-co-glycolide Acid [PLGA] Nanoparticles Loaded with Praziquantel in treatment of experimental murine Schistosomiasis mansoni.

Abstract: Background: Schistosomiasis is a prevailing disease, reported globally in many countries. The classical treatment, although effective, had many disadvantages. Thus, there is a recent interest in nanoparticles [NPs] as a vehicle to increase drug effectiveness and reduce side effects. Aim of the work: The current study was designed to evaluate the in vivo antischistosomal effects of praziquantel-loaded PLGA NPs compared to praziquantel [PZQ] in treatment of experimental murine Schistosomiasis mansoni as regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Our study uses SPL-loaded PLGA NPs which showed better results than free drug. Our results were in agreement with AboSheishaa 76 whose study used PLGA NPs loaded with PZQ. The authors found that PLGA NPs improved the antischistosomal effects of PZQ with highly significant reduction in mean total worm burden, the highest elevation of the percentage of dead ova (95.31%), with complete disappearance of immature ova and the highest reduction of egg load in hepatic tissue by 97.1%.…”
Section: Electron Microscope Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…Our study uses SPL-loaded PLGA NPs which showed better results than free drug. Our results were in agreement with AboSheishaa 76 whose study used PLGA NPs loaded with PZQ. The authors found that PLGA NPs improved the antischistosomal effects of PZQ with highly significant reduction in mean total worm burden, the highest elevation of the percentage of dead ova (95.31%), with complete disappearance of immature ova and the highest reduction of egg load in hepatic tissue by 97.1%.…”
Section: Electron Microscope Studiessupporting
confidence: 92%
“…The authors found that PLGA NPs improved the antischistosomal effects of PZQ with highly significant reduction in mean total worm burden, the highest elevation of the percentage of dead ova (95.31%), with complete disappearance of immature ova and the highest reduction of egg load in hepatic tissue by 97.1%. 76 Another team work 77 potentiate the antischistosomal abilities of the synthetic preparation (the −6,60-dinitrohinokinin (DNHK)) by incorporation to PLGA nanoparticles. The in vitro incubation of adult worms was associated with marked reduction in motor activity and egg production.…”
Section: Electron Microscope Studiesmentioning
confidence: 99%
See 1 more Smart Citation